Trends of laboratory nonhuman primate licensing in China between 2020 and 2024: A national database analysis - Baoxu Ma; Manying Yuan; Wenxian Xiao; Longbao Lv (PLoS ONE, 2026)
Nonhuman primates are critical translational models in biomedical research due to their genetic, anatomical, and physiological similarities to humans. China, once a dominant global supplier of captive-bred laboratory primates, has long maintained a national licensure system to govern their production and use. Despite this, the overall scope, spatial distribution, and institutional landscape of licensing activities for laboratory primates in China remain insufficiently characterized, limiting data-driven governance and resource planning. This study conducted a comprehensive retrospective analysis of all laboratory primate licenses issued in China between 2020 and 2024, based on data retrieved from the China Laboratory Animal Licensing Management System (LALMS). In total, 430 licenses were analyzed across production and utilization categories, temporal dynamics, geographical distribution, and institutional ownership. Utilization licenses constituted 85% of the total, while production licenses accounted for 15%. Licensing activity expanded progressively until 2023 before declining sharply in 2024. Among 31 provincial-level administrative divisions in mainland China, 28 were authorized to produce or utilize laboratory primates. Beijing and Jiangsu emerged as primary centers of licensing activity, particularly for utilization. In contrast, production licenses were predominantly concentrated in Guangxi and Yunnan. Utilization licenses exhibited broader geographic distribution than production licenses, although licensing activity was heavily concentrated in East China (31%), North China (22%), and South China (19%). The majority of licenses were held by commercial enterprises (60%), followed by universities (22%) and research institutes (18%). These findings define the temporal and spatial landscape of laboratory primate licensing in China and generate critical data to inform resource allocation, improve regulatory transparency, and promote the responsible and sustainable integration of primate models into biomedical research.